GmWRKY33a is a hub gene responsive to brassinosteroid signaling that suppresses nodulation in soybean (Glycine max) - Mingliang Yang; Mingliang Yang; Chengjun Lei; Chengjun Lei; Chao Ma; Chao Ma; Xiuming Hou; Xiuming Hou; Mingming Yao; Mingming Yao; Liang Mi; Liang Mi; et al. (Frontiers in Plant Science)
Brassinosteroids (BRs) are key phytohormones influencing soybean development, yet their role in symbiosis remains unclear. Here, the RNA-Seq was used to identify important gene associated with BRs and symbiotic nitrogen fixation, and the function of candidate gene was verified by transgenic hairy roots. The result shows that the RNA-Seq analysis was conducted in which BR signaling was found to suppress nodule formation and many DEGs enriched in immunity-related pathways. WGCNA analyses led to the identification of GmWRKY33a as being responsive to BR signaling in the context of symbiosis establishment. Transgenic hairy roots analyses indicated that GmWRKY33a served as a negative regulator of the establishment of symbiosis. The qRT-PCR analysis confirmed that BR signaling upregulates GmWRKY33a, leading to nodulation suppression and activation of soybean immune responses. In summary, our research revealed that BR suppresses root nodule formation by modulating the immune signaling pathway in soybean roots. We further identified that GmWRKY33a, a crucial transcription factor in BR signaling, plays a negative role in the symbiotic establishment.